Women, Bangladesh and international security : methods, discourses, and policies - Ahmed, Imtiaz, 1958- (The University Press, 2004)
Papers presented at a training workshop of Forum on Women in Security and international Affairs held at Dhaka in 2001; sponsored by Bangladesh Freedom Foundation.